A qualitative study of using movies as a means of escapism between Finns and immigrants in Finland - Attarieh, Maziar (2017)
Escapist use is often considered the main use for movies in Uses and Gratification research, however there is hardly a detailed account on such use, on what the movie audience escape into. The present study, which consists of a research article and a monograph, has tried to utilize a qualitative approach to provide a better understanding of escapist movie viewing. The other aspect of this research is trying to compare such use among Finnish nationals and immigrants in Finland to see how people from different backgrounds might vary in their escapist use of movies. Although no difference between Finns and immigrants living in Finland were seen in the data, due to limitation in its scale, this study cannot confirm that such a difference does not exist. However, roles of platform and content, and more details about what audiences escape into has been discussed in the related research article. The monograph includes more detailed explanation of present study’s research process, and more factors regarding escapist movie viewing that were not predicted while data collection, but seem to be important for having a better understanding of escapism in movie viewers, namely rituals of movie viewing, enhancing one’s experiences, and movie viewing as a social act.